2020
DOI: 10.3390/ani10040567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GABA-T on Reproductive Function in Female Rats

Abstract: This study explored the role of γ-aminobutyric acid transaminase (GABA-T) in the puberty and reproductive performance of female rats. Immunofluorescence technique, quantitative real-time PCR (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA) were used to detect the distribution of GABA-T and the expression of genes and hormones in female rats, respectively. The results showed that GABA-T was mainly distributed in the arcuate nucleus (ARC), paraventricular nucleus (PVN) and periventricular nucleus (PeN) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…GABA plays a major role in a wide range of brain functions, and its dysfunction due to mutations in ABAT has been linked to many different disorders, including epilepsy, psychomotor difficulties, and Alzheimer’s disease [127]. A study on puberty in goats found ABAT to be one of the implicated genes in methylation changes before and after puberty [121], and this gene was also found to be important in puberty and reproductive functions in rats [95].…”
Section: Resultsmentioning
confidence: 99%
“…GABA plays a major role in a wide range of brain functions, and its dysfunction due to mutations in ABAT has been linked to many different disorders, including epilepsy, psychomotor difficulties, and Alzheimer’s disease [127]. A study on puberty in goats found ABAT to be one of the implicated genes in methylation changes before and after puberty [121], and this gene was also found to be important in puberty and reproductive functions in rats [95].…”
Section: Resultsmentioning
confidence: 99%
“…Metestrus, estrus, proestrus, and diestrus are the four stages of the rat estrous cycle [ 20 ]. Progression of the estrous cycle as influenced by the HPG axis is another sign of normal female reproductive development [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 1% sodium pentobarbital solution (60 mg/kg, Sigma, USA) was used to anesthetize rats and deeply positioned in a stereotaxic apparatus. Under aseptic conditions, insert the microsyringe with 2 μl IGFBP-5 protein or saline at a 90° angle into a 2.4 mm posterior to the bregma and 0.5 mm lateral to the midline, 8.6 mm inferior to the skull [ 20 ]. The injection rate was 0.2 μL/min, and the syringe was kept in place for an additional 5 min to allow the injected solution to diffuse into the ARC prior to withdrawal [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Vigabatrin (a small-molecule inhibitor of ABAT) approves for clinical application as an anticonvulsant [15]. Moreover, Vigabatrin has been applied in the study of osteoarthritis and reproduction in mice and has achieved speci c results [16,17]. However, the research progress of ABAT in tumors is insu cient.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between ABAT and some tumors, such as PC, BLBC, ACC, AML, and MB, has been demonstrated [7,10,[18][19][20]. In addition, several potential pathways of ABAT have been discovered in different animal studies, such as dogs, zebra sh, and mice [10,17,[21][22][23]. Although there's quite a bit of clinical data, no evidence showed the pan-cancer association between ABAT and different kinds of human tumors.…”
Section: Introductionmentioning
confidence: 99%